National Partnership for Maternal Safety: Consensus Bundle on Obstetric Hemorrhage. Issue 2 (June 2016) - Main, E.K.; Goffman, B.M.; Kane, L.K.; Bingham, D.; Fontaine, P.L.; Gorlin, J.B.; Lagrew, D.C.; Levy, B.S.
Abstract : ( Anesth Analg. 2015;121(1):142–48) This consensus bundle compiles a selection of guidelines and recommendations for best clinical practices regarding obstetric hemorrhage. The consensus bundle on obstetric hemorrhage was developed by a workgroup of the Partnership for Maternal Safety within the Council on Patient Safety in Women's Health Care, and represents all major women's health care professional organizations. The goal of the partnership is implementation of the safety bundle in every birthing facility in the United States. As it is unlikely that many hospitals will have all of the elements of the consensus bundle in place, it is intended to serve as a checklist from which to work. The consensus bundle is divided into 4 action domains—readiness, recognition and prevention, response, and reporting and systems learning—and encompasses 13 key elements within these domains.